Philippine income taxation - Cenido, Dante Yson. (Manila, Philippines : Conanan Educational Supply, 2002)
This book offers to be the foundation that will trigger the awareness of all readers: Taxation students, CPA reviewees and even businessmen, to the value of taxation, and the role it plays in creating a healthy climate wherein the taxpayers and the state can join hands in shaping our economy.
Part I Principles of taxation -- Chapter 1. General principles of taxation -- Part II Income taxation -- Chapter 2. Definition of terms -- Chapter 3. Personal exemptions -- Chapter 4. Taxation of individuals -- Chapter 5. Taxation of corporations -- Chapter 6. Gross income - individuals and corporations -- Chapter 7. Expenses - individuals and corporations -- Chapter 8. Tax credit -- Chapter 9. Taxation of partnerships and share of partners -- Chapter 10. Installment sales and deferred payment sales -- Chapter 11. Capital gains and losses - general rule -- Chapter 12. Capital gains and losses - sales of shares of stocks -- Chapter 13. Capital gains and losses - sale or other disposition of real property -- Chapter 14. Estate and trust -- Chapter 15. Withholding taxes -- Chapter 16. Deficiency income tax -- Chapter 17. Remedies and penalties -- Chapter 18. Returns and payments of tax -- Chapter 19. Accounting periods and methods, administrative requirements on books, receipts and invoices -- Chapter 20. Reconciliation of net income.
Keywords: INCOME TAXATION -- PHILIPPINES